The Differences in the Composition of Maillard Components between Three Kinds of Sauce-Flavor Daqu - Qi Zhu; Liangqiang Chen; Xiuxin Pu; Guocheng Du; Fan Yang; Jianjun Lu; Zheng Peng; Juan Zhang; Huabin Tu (Fermentation, 2023)
Sauce-flavor Daqu is a saccharifying and fermenting agent for sauce-flavor baijiu. Three kinds of Daqu (White Daqu (WQ), Yellow Daqu (YQ), and Black Daqu (BQ)) with different qualities are formed owing to the stacking fermentation. Maillard reaction is an important factor that causes significant differences among the three kinds of high-temperature Daqu, which is also an important source of flavor substances. However, there is a lack of research on the composition differences of Maillard reaction products in the three types of Daqu. In our study, HS-SPME-GC/MS, Py-GC/MS, and high-throughput sequencing were used to investigate the small molecule volatile Maillard substances, melanoidin (macromolecular Maillard substance) composition, and microbial community of three kinds of Daqu. The results showed that there were significant differences in the composition of Maillard products (furans, pyrazines, and melanoidin structure) between the three kinds of Daqu. The melanoidin was mainly composed of furans, pyrrolopyrazines, phenols, and indoles, the proportions of which were different in the three types of Daqu. BQ contained more Maillard products, making the melanoidin more complex. Kroppenstedtia, Monascus, and Thermoascus were the biomarkers of BQ, which contribute to the Maillard reaction. This study is of great significance to further deepen the understanding of the formation mechanism of BQ.